2018
DOI: 10.1021/acsami.8b09174
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the Surface Recombination and Tuning the Open-Circuit Voltage of Polymer/Fullerene Solar Cells by Implementing an Aggregative Ternary Compound

Abstract: In this work, we present a novel small molecule based on dithienylthienothiadiazole units (named SM1) acting as an efficient component in ternary blend organic solar cells to modify the hole extraction at the interface. Our findings show that the SM1 suppresses the surface recombination and enhances the open-circuit voltage ( V). By introducing SM1 in a host system composed of poly(3-hexylthiophene) (P3HT) and [6,6]-phenyl- C-butyric acid methyl ester (PCBM), we obtained V values of up to 0.75 V and fill facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…And the blend miscibility was calculated using the Flory–Huggins interaction parameters (χ). [ 21,37 ] As shown in Tables S13 and S14, Supporting Information, we observed that with the increment of M w and the reduction of PDI, the surface energy values ( γ s ) of PM6 gradually diminish, leading to the increase of χ values. In general, with the rise of the χ values, the miscibility of the two compounds decreases, leading to more pronounced phase separation and higher domain purity, and vice versa.…”
Section: Resultsmentioning
confidence: 87%
“…And the blend miscibility was calculated using the Flory–Huggins interaction parameters (χ). [ 21,37 ] As shown in Tables S13 and S14, Supporting Information, we observed that with the increment of M w and the reduction of PDI, the surface energy values ( γ s ) of PM6 gradually diminish, leading to the increase of χ values. In general, with the rise of the χ values, the miscibility of the two compounds decreases, leading to more pronounced phase separation and higher domain purity, and vice versa.…”
Section: Resultsmentioning
confidence: 87%
“…113 Alternatively, it has also been suggested that some ternary blends result in a spontaneous segregation of the third component to the surface of the blend resulting in an increased open-circuit voltage and improved charge extraction. 114 The application of our methodology to these ternary material systems will allow the accurate determination of both their energetic and compositional profiles. The ability to cross organic/organic and organic/inorganic interfaces and accurately determine the energetic alignment makes our methodology of great interest to the study of complete photovoltaic devices (including charge extraction layers) as well as tandem organic photovoltaics.…”
Section: Discussionmentioning
confidence: 99%
“…In this contribution we analyzed temperature and light modulated V oc in a series of nonfullerene BHJ solar cells with conventional or inverted device architecture and a systematically tuned effective bandgap E g,eff in a wide range from 1.0 to 1.62 eV. The temperature‐dependent V oc versus light intensity slopes S of the studied systems with the inverted device structure revealed contributions of different recombination mechanisms, i.e., bimolecular recombination, bulk, and surface trap‐assisted (also called Shockley–Read–Hall, SRH) recombination, [ 25–27 ] in various ratios of the respective net recombination rates. By contrast, recombination losses in the reference system, with the conventional device configuration, could be well described only employing the dominant bimolecular recombination mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid development of nonfullerene acceptors, which allow a flexible molecular structure design and with that tunable photoelectrical properties [1][2][3][4][5] triggered the recent record efficiencies of organic solar cells. [6][7][8] The bandgap engineering of nonfullerene acceptors promoted the development of narrow and ultranarrow S of the studied systems with the inverted device structure revealed contributions of different recombination mechanisms, i.e., bimolecular recombination, bulk, and surface trap-assisted (also called Shockley-Read-Hall, SRH) recombination, [25][26][27] in various ratios of the respective net recombination rates. By contrast, recombination losses in the reference system, with the conventional device configuration, could be well described only employing the dominant bimolecular recombination mechanism.…”
Section: Introductionmentioning
confidence: 99%